Los principios procesales de simplificación, eficacia, y economía procesal, frente al expediente electrónico en el sistema SATJE - Vivanco Castro, Andrea Pamela (2023)
The present work studied from a critical perspective the relationship between the procedural principles of simplification, efficiency, and procedural economy, in front of the electronic file in the Ecuadorian Automatic System of Judicial Procedure, which later we will call SATJE, motivating the fundamental issues and examining the statements that are studied for the assistance and analysis of the procedural principles. The chapter began theoretically with the importance of the procedural principles of simplification, efficiency and procedural economy. Additionally, the deficiency of the implementation of the electronic file in the SATJE system was exposed, however, since it is regulated in the current regulations, it is necessary to immediately adjust the system in such a way that it harmonizes the rights of the administrators and their respective technical defenses with the constitutional principles, in charge of facilitating an adequate handling of documents in a short time, without so much bureaucracy in between.